A viral infection explanation for Kawasaki disease in general and for COVID-19 virus-related Kawasaki disease symptoms - Roe, Kevin (Inflammopharmacology, 2020)
SARS-CoV-2, a new virus that appeared in Wuhan, China, in 2019 has approximately an 80% genomic match to the Severe Acute Respiratory Symptom (SARS) virus, which is known to come from a bat virus. Symptoms of Kawasaki disease in general and incomplete Kawasaki disease have been seen in a subset of pediatric patients having a current or previous infection of SARS-CoV-2. A viral infection, such as a SARS-CoV-2 virus infection, could result in extensive antigen–antibody immune complexes that cannot be quickly cleared in a subset of patients and thus create a type III hypersensitivity immune reaction and cause Kawasaki disease or Kawasaki disease symptoms (also known as multisystem inflammatory syndrome) in a subset of patients. Extensive binding of antibodies to viral antigens can create antigen–antibody immune complexes, which, if not eliminated in certain individuals having dysfunctional complement systems, can start inflammatory type III hypersensitivity symptoms, including protease releases that can disrupt epithelium, mesothelium, and endothelium basement membranes, and induce pervasive inflammation throughout the body. This could continue after SARS-CoV-2 infections end if the first wave of protease attacks on basement membranes created new secondary autoantibodies and new uncleared antigen–antibody immune complexes.